UPAYA MENINGKATKAN PELINDUNGAN PEKERJA MIGRAN INDONESIA (PMI) DI NEGARA PENEMPATAN WILAYAH ASIA - Hery Sudarmanto (Bajang Institute, 2022)
After the Indonesian government limits the placement of PMI in the Middle East, placement countries in Asia such as Hong Kong, Taiwan and Malaysia have become countries that are widely hunted by PMI. This study aims to reveal the facts of various problems faced by PMI in the placement country in the Asian region and strategies to overcome these problems. This research approach is qualitative using primary data sources through interviews, FGD and observations. The research results show that there are still many problems faced by PMI even though the placement country already has a legal instrument that is considered better. Intensive approaches and cooperation are needed between the Indonesian government and the state government in the context of enforcement and legal protection for PMI. Coordination and collaboration between the most accurate stakeholders is the most optimal strategy for overcoming PMI problems